English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

3 answers

3/4s² + 1/2s + 1/12 = 0

12(3/4s²) + 12(1/2s) 12(1/12) = 0

9s² + 6s + 1. . . .The Equation

(3s + 1)(3s + 1). . .The factor

- - - - - - -

Roots

3s = - 1

3s/3 = - 1/3

s = - 1/3

The answer is s = - 1/3

- - - - - - - - - - - - - - - -

Quadratic Formula

x = -b ± √b² - 4ac/2a

The equation

9s² + 6s + 1

A = 9
b = 6
c = 1

X = - 6 ± √(6)² - 4(9)(1)/2(9)

x = - 6 ± √36 - 36/18

x = - 6 ± √0 /18

x = - 6 ± 0 / 18

X = - 6/18

x = - 1/3

The answer is x = - 1/3

- - - - - - -s-

2006-12-07 06:31:50 · answer #1 · answered by SAMUEL D 7 · 0 0

1/12(3s+1)^2
s= -1/3

2006-12-07 14:01:13 · answer #2 · answered by      7 · 0 0

0.09983.34.%673/

2006-12-07 14:02:25 · answer #3 · answered by Anonymous · 0 0

fedest.com, questions and answers